2007
DOI: 10.1111/j.1601-0825.2007.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐esophageal manifestations of gastroesophageal reflux

Abstract: Gastroesophageal reflux disease (GERD) is a common medical condition affecting approximately 35–40% of the adult population in the western world. The role of GERD in causing extra‐esophageal symptoms including laryngitis, asthma, cough, chest pain, and dental erosions is increasingly recognized with renewed interest among gastroenterologists and other specialists. Direct injury by mucosal contact, and vagally mediated reflex from distal esophageal acid exposure are the two possible mechanisms by which reflux‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 118 publications
(187 reference statements)
3
52
0
18
Order By: Relevance
“…It has been reported that the prevalence of dental erosion in patients with GERD varies from 5.00 % to 58.41 % (8,24-34), which we corroborated in our series of patients, were a prevalence of 78.9 % was found, higher than the prevalence reported by other authors (8,28,30,31). This is directly related to the severity and duration of the disease; in our cohort, the average time of evolution was 50.09 ± 32.26 months, and the presence of acid reflux was demonstrated in 70.0 % of cases by ph-metry (8,(19)(20)(21)(22)24,34). By comparing the degree of dental erosion with the severity of esophagitis, we found that 75.0 % of the patients with grade N0 and N1 had normal mucosa or grade A esophagitis, whereas patients with N2 and N3 DE were associated with greater frequency to esophagitis stages C and D; the difference was statistically significant (p = 0.021).…”
Section: Discussionsupporting
confidence: 43%
“…It has been reported that the prevalence of dental erosion in patients with GERD varies from 5.00 % to 58.41 % (8,24-34), which we corroborated in our series of patients, were a prevalence of 78.9 % was found, higher than the prevalence reported by other authors (8,28,30,31). This is directly related to the severity and duration of the disease; in our cohort, the average time of evolution was 50.09 ± 32.26 months, and the presence of acid reflux was demonstrated in 70.0 % of cases by ph-metry (8,(19)(20)(21)(22)24,34). By comparing the degree of dental erosion with the severity of esophagitis, we found that 75.0 % of the patients with grade N0 and N1 had normal mucosa or grade A esophagitis, whereas patients with N2 and N3 DE were associated with greater frequency to esophagitis stages C and D; the difference was statistically significant (p = 0.021).…”
Section: Discussionsupporting
confidence: 43%
“…In the past, Koufman described posterior laryngitis in 74% and laryngeal edema with erythema in 60% of all patients with GERD [16] . Tauber et al also reported 85% of GERD-positive patients had posterior laryngitis and 69% had laryngitis with an interarytenoid erythema and edema [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no "gold-standard" for the diagnosis of LPR. Ambulatory 24-h dual or triple probe pH-metry was once considered the best method for reflux testing [16] but the position of the probes makes the measurement not easy to interpret, and there is no consensus about the pathological reflux at the level of laryngopharynx [6] . Moreover, extra-esophageal reflux is also intermittent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Patients can take antacids immediately after heartburn or a sensation of acid reflux into the oral cavity. 36 Patients with erosion should be educated to rinse the mouth with water, sodium bicarbonate, and a fluoride mouthwash immediately after a significant acid challenge. 16 The water will eliminate most of the acid, the sodium bicarbonate will neutralize the remaining acid, and the fluoride mouthwash will help remineralize the etched tooth structure.…”
Section: Preventive Treatmentmentioning
confidence: 99%